The Existence Of Veterans In Displaying Self-Identity (Study Of Intercultural Communication) - Lozi, Pasral; Yanto, Yanto; Risdiyanto, Bayu (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
This research principally aimed to describe the existence of veterans in showing their own self-identities. It was identified in accordance with intercultural communication study. The research was designed as a qualitative study applying deductive data analysis technique. The used method of the research was also descriptive. Furthermore, the data were obtained by conducting interviews, observation, documentation, and intensive literary reviews. The data relating with the identity of veterans in Central Bengkulu Regency were discussed in a comprehensive way from several identity categories which consist of cultural, social, and personal identities. The results showed that the veterans’ presences in Central Bengkulu Regency was established by 3 (three) identities. First, cultural identity of the veterans was obviously reflected in the language acquisition to communicate with other people from different backgrounds. Some languages commonly used were Lembak, Rejang, and Serawai. The second one was about social identity. In this case, the veterans higly never restricted themselves from associating and interacting with other people of community where they lived. The last one was about personal identity. Here, the veterans often showed themselves by using uniforms and full military attributes. In addition, Government of Central Bengkulu Regency remained helping establish the presence of veterans by inviting them to routinely state agendas every year.